Implementasi metode mind mapping untuk meningkatkan kompetensi writing di kelas VII SMP - Lale Andi Yanti Kartini (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2018)
This study aims to describe the implementation of the mind mapping method can improve the writing competence of seventh grade students in junior high school. Data collection is done by observation, interviews, and documentation. Repeat results in the first cycle, 32 of 36 students or 89% of students completed. While in the second cycle, 34 of the 36 students who scored more were the same as the KKM score. There is an increase in learning completeness by 6%. Absorption capacity of the first cycle was 70.69%, and the absorption of the second cycle was 76%. It was concluded that the mind mapping method can improve writing competence in class of seventh grade students in junior high school.